STRATEGI PENERJEMAHAN TAMYĪZ DALAM BUKU AT-TIBYĀN FĪ ĀDĀBI CHAMALATIL-QUR’ĀN KARYA IMAM AN-NAWAWI - Ahmad Falahudin, Abdul Malik (CMES (Center of Middle Eastern Studies), 2017)
This research aims to describe the types of tamyīz (accusative of specification) translation and strategies of translation applied by translator to translate tamyīz on Imam Nawawi’s At-Tibyān Fī Ādābi Chamalatil-Qur’ān (TACQ). The method used in this research is descriptive qualitative. Conducted by observation and marking technique, the collecting data was done by non-interactive method that is identifying and classifying the types of tamyīz found in source language, and matching them with target language translation. The analyzing data uses 3 steps i.e reducing data, presenting, and concluding. The results of this research reveal there are 3 types of tamyīz that are tamyīz asmāul a‘dād, tamyīz muchawwal ‘an mubtada’ and tamyīz muchawwal ‘an maf‘ūl. These types of tamyīz was translated into target language by set of constructs noun phrase, verb phrase, and counted noun phrase. Second, the translator applied 8 strategies of translation to translate tamyīz in TACQ. Among these strategies, the semantic strategy was the most used strategy than others. It was used in 64,29%, whereas structural strategy was used in 35,71%. It’s clear to conclude that the translator favors meaning aspect to translate message clearly and effectively in target language.